The Help of Ego-Documents. Researching the History of Political Culture of Grand Duchy of Lithuania: Case of Jan Cedrowskis Diary - Petrauskė, Kristina (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English]Ego-documents are gaining more popularity and their usages in historiography are getting more dilatable. Despite the fact, that under the title of ego-document are such a well-known sources as diaries, memoires, autobiographies and many more small genres of first person writings. Such sources already were used in historiography for long time, but mainly as a subsidiary material, which would help to collected more data and confirm variable facts. Subjectivity and fictional elements were feared and it was looked upon them with great distance. However using the ego-document method – fictional narrations and inserts, as well as writers subjectivity became these aspects which where most valuable, because they were the keys to the writers personality and their world-view, also such aspects of mental heritage as political culture. With the help of the memoirs of nobleman of Grand Duchy of Lithuania – Jan Cedrowski, we can try to look at the political culture in ego-documents of early-modern time Lithuanian nobleman. Regardless the fact, that these memoirs are very short, they are very vivid and reflects those of the average Lithuanian noblemen. In his memoirs, Jan Cedrowski reflects not only his personal life – youths travels, family life, deaths of relatives, but also the details of his public life, which testifies his political views and culture.